In Memoriam: Elizabeth Ryan, EdD - Paula Termuhlen (Journal of Regional Medical Campuses)
Elizabeth Ruth Ryan, EdD passed away peacefully on October 31, 2024, after a brief illness. She was surrounded by family at the time of her death and was cared for by former students during her hospitalization.